MEANINGS OF SUSTAINABILITY: CATALOGUING SOME DISCOURSES ON “SUSTAINABLE DEVELOPMENT” AND “SUSTAINABILITY” BETWEEN ENVIRONMENTAL EDUCATORS - Correia, Carlos Jorge da Silva; Souza, Flávia dos Santos de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Given that there are many discourses and practices in the environmental field that are considered sustainable nowadays, this paper intends to analyse some of the meanings attributed by Brazil’s environmental educators. For this, we have considered a group of 850 works presented at the Second National Congress of Environmental Education. Standing out within the narratives constructed, based on the analyses made, are those which indicate that sustainability is far from attaining a broad consensus; in fact, despite the significant social impact that discussions on sustainability have recently acquired, we only need to look more closely at this debate to notice the obvious divergences regarding the concept of sustainable development. On the other hand, despite the existing and undeniable divergences, the results of this catalogue also indicate that the notion of sustainable development has acquired, amongst environmental educators, forms that are increasingly settled, or in other words, hegemonic.